Usability Methods for Ensuring Health Information Technology Safety: Evidence-Based Approaches Contribution of the IMIA Working Group Health Informatics for Patient Safety - Borycki, E.; Kushniruk, A.; Nohr, C.; Takeda, H.; Kuwata, S.; Carvalho, C.; Bainbridge, M.; Kannry, J. (Yearbook of Medical Informatics, 2013)
Objectives: Issues related to lack of system usability and potential safety hazards continue to be reported in the health information technology (HIT) literature. Usability engineering methods are increasingly used to ensure improved system usability and they are also beginning to be applied more widely for ensuring the safety of HIT applications. These methods are being used in the design and implementation of many HIT systems. In this paper we describe evidence- based approaches to applying usability engineering methods.Methods: A multi-phased approach to ensuring system usability and safety in healthcare is described. Usability inspection methods are first described including the development of evidence-based safety heuristics for HIT. Laboratory-based usability testing is then conducted under artificial conditions to test if a system has any base level usability problems that need to be corrected. Usability problems that are detected are corrected and then a new phase is initiated where the system is tested under more realistic conditions using clinical simulations. This phase may involve testing the system with simulated patients. Finally, an additional phase may be conducted, involving a naturalistic study of system use under real-world clinical conditions.Results: The methods described have been employed in the analysis of the usability and safety of a wide range of HIT applications, including electronic health record systems, decision support systems and consumer health applications. It has been found that at least usability inspection and usability testing should be applied prior to the widespread release of HIT. However, wherever possible, additional layers of testing involving clinical simulations and a naturalistic evaluation will likely detect usability and safety issues that may not otherwise be detected prior to widespread system release.Conclusion: The framework presented in the paper can be applied in order to develop more usable and safer HIT, based on multiple layers of evidence.
Keywords: Usability testing; clinical simulation; technology-induced error; health information technology; patient safety